Microblading Technique, a Jurisprudential Study of the Fatwas of the Internet - Asma Salmeen Aleryani (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The research deals with the coming down from the juridical issues while it is going down (Microblading), which is a non-surgical cosmetic technique that aims to show the eyebrows more beautifully, by filling in the spaces, defining the shape of the eyebrows and intensifying their hairs, and adding a bend to them when needed, and the shape of the eyebrows can be completely changed With this technique, or rebuilding them for those who do not have hair, and this is done by cutting the skin of the eyebrows superficially and introducing the desired color under it, in the form of hairs, drawn in a 3D manner with a hand tool, to show a hair of hair, simulating the truth, so the eyebrows appear naturally, and it was The Internet has a prominent role in explaining the reality of this technology, through what cosmetic experts and doctors have mentioned, and its ruling also through fatwas and jurisprudential opinions, and these fatwas and opinions differed according to the evidence adopted by each of the two teams, so this research came to shed light on these views Jurisprudence, and the evidence they have inferred, then study it in jurisprudence to reach the legal ruling And among its results: First: The disagreement in the fatwas about the Microblading technique is caused by the disagreement in the origin to which the Microblading technique was referred to regarding whether it is tattooing, or not. Second: There are differences between tattooing and Microblading, but they do not affect judgment. Third: The microblogging technique is forbidden unless necessary.